Geoecological assessment of energy potential of wood raw materials of Belarus - Vorobyov, Dmitry S. (Journal of the Belarusian State University. Geography and Geology, 2017)
The results of geoecological assessment of the energy potential of raw wood Belarus are provided. Significant territorial differences in its location and use for energy purposes have been revealed. Typology of administrative districts of Belarus by total potential of raw wood as a renewable energy source energy and the level of its use is given. Prospective directions of rational use of resources of wood biomass for energy purposes are determined. According to the results of the research recommendations for the appropriate use of wood potential depending on the structure of forest management units are given. Directions for increasing of potential of woody vegetation are proposed. The results of the research can be used in planning the further development and optimization of the territorial location of small power system functioning on wood biomass as well as for maintaining the State inventory of renewable energy sources for an assessment of energy potential of the territory of the administrative regions of the republic, register renewable energy sources and analysis the efficiency of their use.